Livelihood Impact Due to Riverbank Erosion Among the Affected Households Along the River Jamuna of Bangladesh: Livelihood impact due to riverbank erosion (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The present study examines the impacts of riverbank erosion on locals' lives and livelihoods in a particular area of the Jamuna River floodplain of Bangladesh. Riverbank erosion causes thousands of people to be affected, resulting in damage and loss of crops, cattle, housing structures, and farmland. It also erodes public infrastructures and communication networks significantly. This study undertakes empirical methods (including the open-ended questionnaire with a total of 155 households) to demonstrate the study's findings. The lack of adequate measures is the major factor associated with riverbank erosion in the study area. Land property loss becomes one of the major threats among the surveyed families. Some mitigation measures, such as using Geo bags and concrete blocks to protect the banks and operation of dredging machines to divert the water flow, are observed in the study area to reduce erosion. However, these measures are not bringing any effective solution to the local people’s livelihoods due to the slow ongoing work processes.J. Asiat. Soc. Bangladesh, Sci. 49(2): 179-191, December 2023